A CONFIGURATION OF NETWORK FIREWALL AND BANDWITDH MANAGEMENT FOR PRIORITY ZOOM APPLICATIONS USING A MICROTIC ROUTER - Md. Arief Irawan; Rio Septian Hardinata; Nova Mayasari (INFOKUM, 2022)
The problem of slow connection arises if many teachers and employees use it simultaneously so that the use of video conferencing falters due to inappropriate bandwidth usage, it is necessary to mark incoming data packets as internet browsing or as data packets for video conferencing. Therefore, the result of this research is to optimize the network by prioritizing the connection used by video conferencing so that it can be used properly without any disturbance when teachers and other employees use internet access.